Giant M1 resonance on the ground and excited states in 2s1d-shell nuclei - Kachan, A.S.; Vodin, A.N.; Deiev, O.S.; Korda, L.P.; Korda, V.Yu.; Kurhuz, I.V.; Olejnik, S.M.; Timchenko, I.S. (Вопросы атомной науки и техники, 2020)
The gamma decay of the resonance-like structures observed in the reaction of radiative capture of protons by the nuclei ²²Ne, ²⁶Mg, ³⁰Si, ³⁴,³⁶S, and ³⁸Ar in the region of excitation energies of 7…12 MeV was studied. The excitation functions of this reaction were measured. The resonance strengths in the energy range of the accelerated protons Ep = 1.0…3.0 MeV were determined. The obtained discrete distributions of the magnetic dipole γ-transitions on the ground and excited states for the nuclei of the 2s1d-shell have resonance character. Giant M1 resonance on the ground and excited states in the ²³Na, ²⁷Al, ³¹P, ³⁵,³⁷Cl, and ³⁹K nuclei has been identified. The position of the M1 resonance on excited states coincides with that predicted by the Brink-Axel hypothesis for nuclei that are at the beginning of the subshell.